Making Meaningful Use of Price Transparency Data: Describing Price Variation of Spine Surgery and Imaging in a Single System. Issue 3 (23rd September 2022) - Olufawo, Michael O.; Evans, Sophia S.; Stecher, Priscilla T.; Youkilis, Samuel L.; Dibble, Christopher F.; Greenberg, Jacob K.; Ray, Wilson Z.; Hamilton, Barton H.; Leuthardt, Eric C.
Abstract : Price transparency is an increasingly popular solution for high healthcare expenditures in the United States, but little is known about its potential to facilitate patient price shopping. Our objective was to analyze interhospital and interpayer price variability in spine surgery and spine imaging using newly public payer-specific negotiated charges (PNCs). We selected a subset of billing codes for spine surgery and spine imaging at 12 hospitals within a Saint Louis metropolitan area healthcare system. We then compared PNCs for these procedures and tested for significant differences in interhospital and interinsurer IQR using the Mann–Whitney U Test. We found significantly greater IQRs of PNCs as a factor of the insurance plan than as a factor of the hospital for cervical spinal fusions (interinsurer IQR $8256; interhospital IQR $533; P < .0001), noncervical spinal fusions (interinsurer IQR $28 423; interhospital IQR $5512; P < .001), computed tomographies of the lower spine (interinsurer IQR $595; interhospital IQR $113; P < .0001), and MRIs lower spinal canal (interinsurer IQR $1010; interhospital IQR $158; P < .0001). There was no significant difference between the interinsurer IQR and the interhospital IQR for lower spine x-rays (interinsurer IQR $107; interhospital IQR $67; P = .0543). Despite some between-hospital heterogeneity, we show significantly higher price variability between insurers than between hospitals. Our single system analysis limits our ability to generalize, but our results suggest that savings depend more on hospital and provider negotiations than patient price shopping, given the difficulty of switching insurers.